Biochemical Studies of the Smooth-Rough Mutation in Salmonella minnesota - Lüderitz, O. (1965)
Lüderitz, O. (Max-Planck-Institut für Immunbiologie, Frieburg, Germany), H. J. Risse, H. Schulte-Holthausen, J. L. Strominger, I. W. Sutherland, and O. Westphal. Biochemical studies of the smooth-rough mutation in Salmonella minnesota. J. Bacteriol. 89:343–354. 1965.—A comparative study of the O antigen from the smooth strain of Salmonella minnesota and of the two R antigens derived from two rough forms of S. minnesota (strains R 60 and R 345) has been carried out. The O-specific polysaccharide of the smooth form is composed of heptose, galactose, glucose, glucosamine, galactosamine, and ketodeoxyoctanoate (KDO). R 60 polysaccharide contains KDO, heptose, galactose, glucose, and glucosamine, whereas the R 345 polysaccharide contains only KDO, heptose, galactose, and glucose. Serologically, R 345 and R 60 polysaccharides belong to serogroups R I and R II, respectively. Enzymatic studies revealed that the acetylgalactosamine-synthesizing enzyme, uridine diphosphate-N-acetylglucosamine-4-epimerase, is present in wild-type and R 345 cells but is absent from R 60 cells. Two distinct polysaccharides were obtained from the R 345 cells: a polysaccharide derived from the R antigen (lipopolysaccharide) containing no galactosamine and exerting R specificity, and a soluble polysaccharide containing galactosamine and exerting O specificity. The structure of O and R antigens is discussed, together with the general significance of the results for the biosynthesis of the O antigens of the genus Salmonella.